Compatibility of Bt biopesticides and adjuvants for Spodoptera frugiperda control - dos Santos, Cicero Antônio Mariano [UNESP] (2021)
Spodoptera frugiperda is a pest of economic importance for several crops with resistance reports to Bt crops and pesticides. Eco-friendly Bt biopesticides may be an alternative to chemical insecticides due to their selectivity and specificity. However, the efficacy of Bt biopesticides may be influenced by the association with other chemicals, such as adjuvants. This study evaluated the compatibility and toxicity of Bt biopesticides mixed with adjuvants for the control of S. frugiperda. The treatments included the association of Dipel SC and Dipel PM with adjuvants. Compatibility tests were used to evaluate the Bt mixture. Bt suspensions obtained from mixtures of Bt and adjuvants at 106 and 3 × 108 spores/mL−1 were used to evaluate S. frugiperda mortality and distilled water was used as the control. The addition of the adjuvant LI increased growth and sporulation, indicating compatibility with Bt biopesticides. The other adjuvants were toxic to reducing Bt growth and sporulation. Only the mixture of Bt with LI and Bt alone was effective to S. frugiperda. The addition of adjuvants to Bt biopesticide affect the Bt sporulation, growth and mortality.